The role of diaspora networks in opportunity exploitation by ethnic entrepreneurs in Finland - Jafarov, Elkhan (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The thesis explores the role of diaspora network in opportunity exploitation by ethnic entrepreneurs in Finland. The purpose of this study is to how ethnic entrepreneurs in Finland can exploit diaspora networks and how significant support of these networks in comparison with governmental and other official institutional support. Increased mobility of the global population and number of immigrants all around the world contribute into interest of academics to this topic. At the same time, in comparison with other European countries for Finland this phenomenon is new. However, increasing number of immigrants add to academic interest to this topic. The theoretical background of this thesis consists of the collection of studies done on diaspora networks and ethnic entrepreneurs as internationally as in Finland. The concept of cooperation between diaspora and ethnic entrepreneurs describes how diaspora can support ethnic entrepreneur and emphasize importance of diaspora ties for business. At the end of the theoretical section theoretical a special grid was proposed as summary of the academic literature review. The empirical research for this study is based on the interviews with five ethnic entrepreneurs in Finland. Empirical data was analyzed and compared with the similar studies done internationally. During the interviews analyses were stressed aspects of the significance of governmental and other official institutional support. During the interviews analyses were stressed aspects of the significance of the governmental and other official institutional support. According to the main findings diaspora can play positive and in some cases crucial role in the business of ethnic entrepreneurs in Finland. Moreover, diaspora can be a facilitator of internationalization of ethnic entrepreneurs. At the same time, there are several factors which might increase or decrease role of diaspora. The ways of the utilization of diaspora network were combined in the empirical grid. The study enhance understanding of the challenges of ethnic entrepreneurs and provides certain recommendations for the policy makers, ethnic entrepreneurs and managers of official institutions involved in cooperation with ethnic entrepreneurs